A heuristic energy-aware approach for hard real-time systems on multi-core platforms - He, Da; Müller, Wolfgang (Microprocessors and Microsystems - Embedded Hardware Design 37(6-7))

Embedded Systems: Design, Analysis and Verification. Proceedings of the 4th IFIP TC10 International Embedded Systems Symposium, IESS 2013, Paderborn, Germany, June 2013

Organic Programming of Real-Time Operating Systems - Khaluf, Lial; Rammig, Franz-Josef (The Ninth International Conference on Autonomic and Autonomous Systems)

Methods for the Design and Development - Anacker, Harald; Dellnitz, Michael; Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Horenkamp, Christian; Kleinjohann, Lisa; Kleinjohann, Bernd; Korf, Sebastian; Krüger, Martin; Müller, Wolfgang; et al. (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Learning Efficient Information Extraction on Heterogeneous Texts - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the Sixth International Joint Conference on Natural Language Processing)

Information Extraction as a Filtering Task - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the 22nd ACM International Conference on Conference on Information & Knowledge Management)

Automatic Pipeline Construction for Real-Time Annotation - Wachsmuth, Henning; Rose, Mirko; Engels, Gregor (14th International Conference on Intelligent Text Processing and Computational Linguistics)

Practical algorithms for clustering and modeling large data sets - Analysis and improvements - Kuntze, Daniel

An Approach for Determining Optimal Contrast in Visual Cryptography - Juhnke, Jakob; Lefmann, Hanno; Strehl, Volker

Improved Side Channel Attacks on Pairing Based Cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Constructive Side-Channel Analysis and Secure Design)

On the Analysis of Cryptographic Assumptions in the Generic Ring Model - Jager, Tibor; Schwenk, Jörg (J. Cryptology)

Practical Signatures from Standard Assumptions - Böhl, Florian; Hofheinz, Dennis; Jager, Tibor; Koch, Jessica; Hong Seo, Jae; Striecks, Christoph (Advances in Cryptology - EUROCRYPT 2013, 32nd Annual International Conference on the Theory and Applications of Cryptographic Techniques, Athens, Greece, May 26-30, 2013. Proceedings)

One Bad Apple: Backwards Compatibility Attacks on State-of-the-Art Cryptography - Jager, Tibor; Paterson, Kenneth G.; Somorovsky, Juraj (20th Annual Network and Distributed System Security Symposium, NDSS 2013, San Diego, California, USA, February 24-27, 2013)

Bounded Model Checking of Graph Transformation Systems via SMT Solving - Isenberg, Tobias; Steenken, Dominik; Wehrheim, Heike (Formal Techniques for Distributed Systems - Joint IFIP WG 6.1 International Conference, {FMOODS/FORTE} 2013, Held as Part of the 8th International Federated Conference on Distributed Computing Techniques, DisCoTec 2013, Florence, Italy, June 3-5, 2013. Proceedings)

SPIN as a Linearizability Checker under Weak Memory Models - Travkin, Oleg; Mütze, Annika; Wehrheim, Heike (Hardware and Software: Verification and Testing - 9th International Haifa Verification Conference, HVC 2013, Haifa, Israel, November 5-7, 2013, Proceedings)

A High-Level Semantics for Program Execution under Total Store Order Memory - Dongol, Brijesh; Travkin, Oleg; Derrick, John; Wehrheim, Heike (Theoretical Aspects of Computing - ICTAC 2013 - 10th International Colloquium, Shanghai, China, September 4-6, 2013. Proceedings)

Temporal Reconfiguration Plans for Self-Adaptive Systems - Ziegert, Steffen; Wehrheim, Heike (Software Engineering 2013: Fachtagung des GI-Fachbereichs Softwaretechnik, 26. Februar - 2. März 2013 in Aachen)

11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung - Gausemeier, Jürgen; Grafe, Michael; Meyer auf der Heide, Friedhelm

Approaches for an informational separation of powers in learning platforms - Keil, Reinhard; Winkelnkemper, Felix

„Do You Speak Usability?“ – Aktueller Stand des Glossars und des Curriculums für den „Certified Professional for Usability and User Experience (CPUX)“ der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter; Polkehn, Knut

Contextual tagging in the coactive knowledge organization - K {\ "u} hnel, Birger

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten

Computer science and education - A struggle for creative sovereignty in society? - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix (FIfF-Kommunikation)

Media contexts - context media - Keil, Reinhard

A Taxonomy-Based Approach Towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard

Adapting Hardware Systems by Means of Multi-Objective Evolution - Kaufmann, Paul
Reconfigurable circuit devices have opened up a fundamentally new way of creating adaptable systems. Combined with artificial evolution, reconfigurable circuits allow an elegant adaptation approach to compensating for changes in the distribution of input data, computational resource errors, and variations in resource requirements. Referred to as ``Evolvable Hardware'' (EHW), this paradigm has yielded astonishing results for traditional engineering challenges and has discovered intriguing design principles, which have not yet been seen in conventional engineering. In this thesis, we present new and fundamental work on Evolvable Hardware motivated by the insight that Evolvable Hardware needs to compensate for events with different change rates. To solve the challenge of different adaptation speeds, we propose a unified adaptation approach based on multi-objective evolution, evolving and propagating candidate solutions that are diverse in objectives that may experience radical changes. Focusing on algorithmic aspects, we enable Cartesian Genetic Programming (CGP) model, which we are using to encode Boolean circuits, for multi-objective optimization by introducing a meaningful recombination operator. We improve the scalability of CGP by objectives scaling, periodization of local- and global-search algorithms, and the automatic acquisition and reuse of subfunctions using age- and cone-based techniques. We validate our methods on the applications of adaptation of hardware classifiers to resource changes, recognition of muscular signals for prosthesis control and optimization of processor caches.

Das Verteilungsproblem für mechatronische Systeme - Hüwe, Marcus

Simulationsgestützter Entwurf für Elektrofahrzeuge - Farshizadeh, Emad; Briese, Hermann; Steinmann, David; Stockmann, Lars; Beringer, Steffen; Holler, Dominik; Klobedanz, Kay; Heinzemann, Christian; Peter, Klaus; Leuer, Michael (8. Dortmunder Autotag)
Das Thema Elektromobilität hat in der Fahrzeugindustrie in den letzten Jahren viel Aufmerksamkeit erhalten. Gerade im Bereich der Entwicklung von Steuergeräte-Software ist der Bedarf an frühzeitiger Absicherung hoch. Nur so können Produkteinführungszeiten minimiert und effektiv Entwicklungskosten eingespart werden. Komplexe Werkzeugketten und die verteilte Entwicklung erschweren den Prozess und verlängern die Entwicklungszeit. Das Förderprojekt „Simulationsgestützter Entwurf für Elektrofahrzeuge“, kurz „E-Mobil“, nimmt sich der Herausforderungen einer verteilten Entwicklung von Steuergeräte-Software an. Vier Projektpartner aus Industrie und Forschung untersuchen die Besonderheiten sowohl bzgl. des Entwurfsprozesses, als auch der beteiligten Entwurfswerkzeuge im Vergleich zur konventionellen Fahrzeugentwicklung. Im Fokus stehen die Modellierung und die simulationsgestützte Absicherung in frühen Entwurfsstadien. Die Modellierung umfasst Regelungssoftware sowie die für die Simulation nötigen elektrischen und mechatronischen Komponenten. Die vorliegende Arbeit stellt die Kernthemen sowie aktuelle Ergebnisse aus dem Projekt vor.

Combining Scenario-based and Architecture-based Timing Requirements - Koch, Thorsten
Die in der Automobilindustrie verwendeten eingebetteten Systeme gehören zu den komplexesten eingebetteten Systemen. Die Automobilhersteller sind in der Entwicklung ständig bemüht sowohl die Sicherheit und den Komfort des Fahrers also auch der anderen Insassen zu verbessern. Die meisten der entwickelten Systeme sind sowohl zeit- als auch sicherheitskritisch. Einer Studie von Mercedes-Benz zufolge resultieren 80% der Innovationen in der Automobilbranche aus neuen Elektronikkomponenten, deren Funktionen zu 90% durch Software realisiert wird. Um die steigende Komplexität in der Entwicklung von eingebetteten Systemen zu beherrschen wird in der Automobilbranche immer öfter die modelbasierte Softwareentwicklung anstelle der klassischen Programmierung eingesetzt. Im Requirements Engineering, der ersten Phase der Entwicklung eines Produktes, werden die Anforderungen gesammelt und dokumentiert. Die Dokumentation erfolgt mittels natürlicher Sprache. Modellbasierte Ansätze werden heutzutage höchstens unterstützend eingesetzt. Während des Requirements Engineerings muss der Requirements Engineer sowohl die funktionalen Anforderungen an das zu entwickelnde System als auch seine zeitlichen Anforderungen spezifizieren und analysieren. Die funktionalen Anforderungen umfassen dabei insbesondere die Kommunikation zwischen den verschiedenen Teilsystemen. Szenarien stellen eine intuitive Möglichkeit zur Modellierung von funktionalen Anforderungen dar. Im Rahmen dieser Arbeit wird ein modellbasierter Ansatz zur Modellierung von Szenarien verwendet. Anforderungen an das zeitliche Verhalten werden innerhalb der Architektur spezifiziert. Dazu stehen in der Automobilbranche Architekturbeschreibungssprachen wie EAST-ADL zur Verfügung. Obwohl sowohl funktionale als auch zeitliche Anforderungen an das System spezifiziert und analysiert werden müssen, existiert bisher keine Methodik, die beide Ansätze miteinander kombiniert. Aus diesem Grund wurde im Rahmen dieser Arbeit eine neue Requirements Engineering Methodik entwickelt, die eine systematische und ganzheitliche Spezifikation und Analyse der funktionalen und zeitlichen Anforderungen bereitstellt. Wir haben zwei Modelltransformationen entwickelt, um den Requirements Engineer beim Übergang von den funktionalen zu den zeitlichen Anforderungen zu unterstützen. Die vorliegende Arbeit wird durch eine Evaluierung der Methodik, sowie der Modelltransformationen auf Basis eines Komfortsteuergerätes abgerundet.

Darstellung heterogener 3-D-Szenen in Echtzeit - Petring, Ralf; Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)
Viele virtuelle 3-D-Szenen im industriellen Bereich sind nicht gleichmäßig strukturiert, z.B. weil sie eine stark unterschiedliche Dichteverteilung der Polygone aufweisen. Für solch heterogene Daten existiert kein Algorithmus, der die Gesamtheit der Daten sowohl schnell als auch mit guter Qualität darstellen kann. Die Auswahl der richtigen Algorithmen für einzelne Szenenteile durch einen Experten ist zeitintensiv und in vielen Visualisierungssystemen nicht umzusetzen. Um dieses Problem zu lösen, setzt das hier vorgestellte Multi-Algorithmen-Rendering verschiedene Renderingalgorithmen gleichzeitig ein, um eine virtuelle 3-D-Szene darzustellen. Das Verfahren unterteilt die Szene dafür in einem Vorverarbeitungsschritt automatisch in geeignete Teilregionen und bestimmt deren Eigenschaften. Diese Daten werden zur Laufzeit dazu genutzt, um ständig für den aktuellen Standpunkt des Betrachters eine Abschätzung der Qualität und Laufzeit der zur Auswahl stehenden Renderingalgorithmen zu berechnen. Durch die Lösung eines Optimierungsproblems kann so bei vorgegebener Bildrate durch die passende Zuordnung der Algorithmen zu den Regionen die Bildqualität optimiert werden – bei automatischer Anpassung an die Leistungsfähigkeit der eingesetzten Hardware. In einer experimentellen Evaluierung vergleichen wir die Laufzeit und Bildqualität des Verfahrens mit denen verbreiteter Standardrenderingverfahren.

Spherical visibility sampling : preprocessed visibility for occlusion culling in complex 3D scenes - Eikel, Benjamin

Algorithmische Grundlagen für die Selbstorganisation von Roboterschwärmen - Meyer auf der Heide, Friedhelm (11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung

On the Admission of Dependent Flows in Powerful Sensor Networks - Cohen, R.; Nudelman, I.; Polevoy, Gleb (Networking, IEEE/ACM Transactions on)
In this paper, we define and study a new problem, referred to as the Dependent Unsplittable Flow Problem (D-UFP). We present and discuss this problem in the context of large-scale powerful (radar/camera) sensor networks, but we believe it has important applications on the admission of large flows in other networks as well. In order to optimize the selection of flows transmitted to the gateway, D-UFP takes into account possible dependencies between flows. We show that D-UFP is more difficult than NP-hard problems for which no good approximation is known. Then, we address two special cases of this problem: the case where all the sensors have a shared channel and the case where the sensors form a mesh and route to the gateway over a spanning tree.
Keywords: Approximation algorithms; Approximation methods; Bandwidth; Logic gates; Radar; Vectors; Wireless sensor networks; Dependent flow scheduling; sensor networks

A framework for enhancing dependability in self-x systems by Artificial Immune Systems - Rammig, Franz; Stahl, Katharina; Vaz, Gavin Francis (IEEE Int. Symp. on Object/component/service-oriented Real-time distributed Computing (ISORC))

FPGA Implementation of a Second-Order Convolutive Blind Signal Separation Algorithm - Kasap, Server; Redif, Soydan (Proc. IEEE Signal Processing and Communications Conf. (SUI))

Novel Field-Programmable Gate Array Architecture for Computing the Eigenvalue Decomposition of Para-Hermitian Polynomial Matrices - Kasap, Server; Redif, Soydan (IEEE Trans. on Very Large Scale Integration (VLSI) Systems)

Competitive throughput in multi-hop wireless networks despite adaptive jamming - W. Richa, Andréa; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Distributed Computing)

Corona: A stabilizing deterministic message-passing skip list - Mohd Nor, Rizal; Nesterenko, Mikhail; Scheideler, Christian (Theor. Comput. Sci.)

An Efficient and Fair MAC Protocol Robust to Reactive Interference - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (IEEE/ACM Trans. Netw.)

Quelltextgenerierung für LEGO Mindstorms-Roboter - Geismann, Johannes (Berichtsband der Informatiktage 2013: Smarte Sichten, smarte Schichten)
Die Komplexität von mechatronischen Systemen wird stetig größer. MechatronicUML (MUML) ist eine Methode zur Entwicklung für Software von mechatronischen Systemen. Im Rahmen einer Bachelorarbeit wurde ein bestehender Quelltextgenerator für MUML-Modelle so erweitert, dass Quelltext für ein Echtzeitbetriebssystem generiert werden kann, welches auf einem LEGO Mindstorms-Roboter installiert ist.

Modulare Leistungsprognose von Kompaktsteuerungen - Frieben, Jens; Heutger, Henning; Meyer, Matthias; Becker, Steffen (9. Paderborner Workshop Entwurf mechatronischer Systeme)

An evaluation testbed for adaptive, topology-aware deployment of elastic applications - Keller, Matthias; Robbert, Christoph; Peuster, Manuel (Proceedings of the ACM SIGCOMM 2013 conference on SIGCOMM)

CROWD: An SDN Approach for DenseNets - Ali-Ahmad, Hassan; Cicconetti, Claudio; de la Oliva, Antonio; Draxler, Martin; Gupta, Rohit; Mancuso, Vincenzo; Roullet, Laurent; Sciancalepore, Vincenzo (2013 Second European Workshop on Software Defined Networks)

A Scalable Redundant TDMA Protocol for High-Density WSNs Inside an Aircraft - Blanckenstein, Johannes; Garcia-Jimenez, Javier; Klaue, Jirka; Karl, Holger (Lecture Notes in Electrical Engineering)

Cliquenbildung in verteilten Systemen - Blumentritt, Fritz

Adding Capacity-Aware Storage Indirection to Homogeneous Distributed Hash Tables - Wette, P.; Graffi, K. (2013 Conference on Networked Systems)

OpenNetInf - prototyping an information-centric Network Architecture - Dannewitz, Christian; Herlich, Matthias; Karl, Holger (37th Annual IEEE Conference on Local Computer Networks -- Workshops)

Denser Networks for the Future Internet, the CROWD Approach - de la Oliva, Antonio; Morelli, Arianna; Mancuso, Vincenzo; Draexler, Martin; Hentschel, Tim; Melia, Telemaco; Seite, Pierrick; Cicconetti, Claudio (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering)

Intelligenz in der Produktion - Spitzencluster it's OWL als Wegbereiter für Industrie 4.0 - Dumitrescu, Roman; Kühn, Arno (Markt&Technik Summit Industrie 4.0, München, 16. - 17. Okt. 2013)

Von der Anforderungserfassung bis zur Funktionsstruktur - Ein Systems Engineering-Vorgehen für die industrielle Praxis - Schmitt, Nicolas; Kaiser, Lydia; Dumitrescu, Roman; Hofmann, Maik (Tag des Systems Engineering)

Hybrid-Actuated Finger Prosthesis with Tactile Sensing - Low, Cheng Yee; Kasim, Mohamad Amlie Abu; Koch, Torben; Dumitrescu, Roman; Yussof, Hanafiah; Jaafar, Roseleena; Jaafar, Ahmed; Aqilah, Ahsana; Ng, Kok Mun (International Journal of Advanced Robotic Systems)

Strategy Planning of Collaborative Humanoid Soccer Robots based on Principle Solution - Low, Cheng; Aldemir, Mustafa; Aziz, Norheliena; Dumitrescu, Roman; Anacker, Harald (Journal of Production Engineering Research & Development (PERE) 7)

The Need to Start Research Education Early - Joel, W. J. (IEEE Computer Graphics and Applications)

Information Visualization Courses for Students with a Computer Science Background - Kerren, A. (IEEE Computer Graphics and Applications)

Building Virtual Worlds Carrying on the Legacy of Randy Pausch's "Head Fake" - Schell, J.; Klug, C. (IEEE Computer Graphics and Applications)

Network of Information (NetInf) - An information-centric networking architecture - Dannewitz, Christian; Kutscher, Dirk; Ohlman, B; Farrell, Stephen; Ahlgren, Bengt; Karl, Holger (Computer Communications)

Improving Cooperative Transmission Feasibility by Network Reconfiguration in Limited Backhaul Networks - Dräxler, Martin; Biermann, Thorsten; Karl, Holger (International Journal of Wireless Information Networks)

Trade-off between latency and coverage in cooperative radio access networks - Hohenberger, Till; Herlich, Matthias; Karl, Holger (IEEE International Conference on Advanced Networks and Telecommunications Systems, ANTS 2013, Kattankulathur, India, December 15-18, 2013)

NetIDE: First Steps towards an Integrated Development Environment for Portable Network Apps - M. Facca, Federico; Salvadori, Elio; Karl, Holger; R. Lopez, Diego; Arranda Gutierrez, Pedro; Kostic, Dejan; Riggio, Roberto (Second European Workshop on Software Defined Networks, EWSDN 2013, Berlin, Germany, October 10-11, 2013)

The playground of Wireless Dense networks of the future - Cicconetti, Claudio; Morelli, Arianna; Dräxler, Martin; Karl, Holger; Mancuso, Vincenzo; Sciancalepore, Vincenzo; Gupta, Rohit; de la Oliva, Antonio; Isabel Sanchez, M.; Serrano, Pablo; Roullet, Laurent (2013 Future Network & Mobile Summit, Lisboa, Portugal, July 3-5, 2013)

A topology-aware adaptive deployment framework for elastic applications - Keller, Matthias; Peuster, Manuel; Robbert, Christoph; Karl, Holger (17th International Conference on Intelligence in Next Generation Networks, ICIN 2013, Venice, Italy, October 15-16, 2013)

Energy-Efficient Assignment of User Equipment to Cooperative Base Stations - Herlich, Matthias; Karl, Holger (ISWCS 2013, The Tenth International Symposium on Wireless Communication Systems, Ilmenau, Germany, August 27-30, 2013)

Vorgehensmodelle 2013: Vorgehensmodelle - Anspruch und Wirklichkeit - Proceedings der 20. Tagung der Fachgruppe Vorgehensmodelle im Fachgebiet Wirtschaftsinformatik (WI-VM) der Gesellschaft für Informatik e.V., Lörrach (Germany)

Cross-layer scheduling for multi-quality video streaming in cellular wireless networks - Dräxler, Martin; Karl, Holger (2013 9th International Wireless Communications and Mobile Computing Conference, IWCMC 2013, Sardinia, Italy, July 1-5, 2013)

Anticipatory Buffer Control and Quality Selection for Wireless Video Streaming - Dräxler, Martin; Blobel, Johannes; Dreimann, Philipp; Valentin, Stefan; Karl, Holger (CoRR)

Ensuring Consistency Among Business Goals and Business Process Models - Nagel, Benjamin; Gerth, Christian; Post, Jennifer; Engels, Gregor (Proceedings of the 17th IEEE International EDOC Conference (EDOC'13))
The paradigm of service-oriented architectures has emerged as an architectural style for designing enterprise applications. Requirements engineering for such applications comprises the specification of business goal models representing stakeholder objectives and the operationalization to business process models that specify the required composition of services. Inconsistencies between business goals and derived business processes can lead to service compositions that are not in line with the actual stakeholder objectives. For preserving consistency it is required to consider logical and temporal dependencies among goals (e.g. the order in which they need to be achieved) in the derivation of business processes. In previous work, we provided a technique for the elicitation and specification of dependencies between business goals. Extending this approach, we aim at validating the consistency between business goal models and business process models regarding these dependencies. In this paper, we present a pattern-based approach for the automated generation of verifiable business process quality constraints from business goal models. We describe how these constraints can be used to check the consistency between business goals and business processes and demonstrate the applicability of our approach in a case study by using the implemented tool support.

Modellbasierte Bewertung von Testprozessen nach TPI NEXT® mit Geschäftsprozess-Mustern - Schumacher, Claudia; Engels, Gregor; Güldali, Baris; Niehammer, Markus; Hamburg, Matthias (Proceedings of the conference on Software Enginneering, Fachtagung des GI Fachbereichs Softwaretechnik (SE 2013), Aachen (Germany))

On-the-Fly Computing - Das Entwicklungs- und Betriebsparadigma für Softwaresysteme der Zukunft - Engels, Gregor (Software Engineering 2013)

Automated Service Composition for On-the-Fly SOAs - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the 11th International Conference on Service Oriented Computing (ICSOC'13))

High-Quality Specification of Self-Adaptive Software Systems - Luckey, Markus; Engels, Gregor (Proceeding of the 8th international symposium on Software engineering for adaptive and self-managing systems)

Decision Support via Automated Metric Comparison for the Palladio-based Performance Blame Analysis - Brüseke, Frank; Becker, Steffen; Engels, Gregor (Proceedings of the 4th ACM/SPEC International Conference on Performance Engineering (ICPE 2013), Prague (Czech Republic))

Performance Analysis of Self-Adaptive Systems for Requirements Validation at Design-Time - Becker, Matthias; Luckey, Markus; Becker, Steffen (Ninth International ACM Sigsoft Conference on the Quality of Software Architectures)

Integrating Coverage Analysis into Test-driven Development of Model Transformations - Küster, Jochen; Kovács, Dániel; Bauer, Eduard; Gerth, Christian

Automated Service Discovery and Composition for On-the-Fly SOAs - Huma, Zille; Gerth, Christian; Engels, Gregor

Konzeption modellbasierter Benutzungsschnittstellen für verteilte Selbstbedienungssysteme - Yigitbas, Enes; Gerth, Christian; Sauer, Stefan (Informatik 2013, 43. Jahrestagung der Gesellschaft für Informatik e.V. (GI), Informatik angepasst an Mensch, Organisation und Umwelt, 16.-20. September 2013, Koblenz, Deutschland)

A Taxonomy-Based Approach towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard (Distributed, Ambient, and Pervasive Interactions)

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten (Design, User Experience, and Usability. Design Philosophy, Methods, and Tools)

Do You Speak Usability? - Aktueller Stand des Glossars und des Curriculums für den Certified Professional for Usability and User Experience (CPUX) der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter (Jahresband Usability Professionals)

Zero Overhead Runtime Monitoring - Wonisch, Daniel; Schremmer, Alexander; Wehrheim, Heike (Proceedings of the 11th International Conference on Software Engineering and Formal Methods (SEFM))
Runtime monitoring aims at ensuring program safety by monitoring the program's behaviour during execution and taking appropriate action before a program violates some property.Runtime monitoring is in particular important when an exhaustive formal verification fails. While the approach allows for a safe execution of programs, it may impose a significant runtime overhead.In this paper, we propose a novel technique combining verification and monitoring which incurs no overhead during runtime at all. The technique proceeds by using the inconclusive result of a verification run as the basis for transforming the program into one where all potential points of failure are replaced by HALT statements. The new program is safe by construction, behaviourally equivalent to the original program (except for unsafe behaviour),and has the same performance characteristics.

Which Flows Are Hiding Behind My Wildcard Rule? Adding Packet Sampling to OpenFlow - Wette, Philip; Karl, Holger (Proceedings of the ACM SIGCOMM '13)
In OpenFlow [1], multiple switches share the same control plane which is centralized atwhat is called the OpenFlow controller. A switch only consists of a forwarding plane. Rules for forwarding individual packets (called ow entries in OpenFlow) are pushed from the controller to the switches. In a network with a high arrival rate of new ows, such as in a data center, the control trac between the switch and controller can become very high. As a consequence, routing of new ows will be slow. One way to reduce control trac is to use wildcarded ow entries. Wildcard ow entries can be used to create default routes in the network. However, since switches do not keep track of ows covered by a wildcard ow entry, the controller no longer has knowledge about individual ows. To nd out about these individual ows we propose an extension to the current OpenFlow standard to enable packet sampling of wildcard ow entries.

Verteilte Erstellung und Aktualisierung von Schlüsselservern in identitätsbasierten Verschlüsselungssystemen - Tezer, Alina

Towards Duality of Multicommodity Multiroute Cuts and Flows: Multilevel Ball-Growing - Kolman, Petr; Scheideler, Christian (Theory of Computing Systems)
An elementary h-route ow, for an integer h 1, is a set of h edge- disjoint paths between a source and a sink, each path carrying a unit of ow, and an h-route ow is a non-negative linear combination of elementary h-routeows. An h-route cut is a set of edges whose removal decreases the maximum h-route ow between a given source-sink pair (or between every source-sink pair in the multicommodity setting) to zero. The main result of this paper is an approximate duality theorem for multicommodity h-route cuts and ows, for h 3: The size of a minimum h-route cut is at least f=h and at most O(log4 k f) where f is the size of the maximum h-routeow and k is the number of commodities. The main step towards the proof of this duality is the design and analysis of a polynomial-time approximation algorithm for the minimum h-route cut problem for h = 3 that has an approximation ratio of O(log4 k). Previously, polylogarithmic approximation was known only for h-route cuts for h 2. A key ingredient of our algorithm is a novel rounding technique that we call multilevel ball-growing. Though the proof of the duality relies on this algorithm, it is not a straightforward corollary of it as in the case of classical multicommodity ows and cuts. Similar results are shown also for the sparsest multiroute cut problem.

Token Dissemination in Geometric Dynamic Networks - Abshoff, Sebastian; Benter, Markus; Cord-Landwehr, Andreas; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics, ALGOSENSORS 2013, Sophia Antipolis, France, September 5-6, 2013, Revised Selected Papers)
We consider the k-token dissemination problem, where k initially arbitrarily distributed tokens have to be disseminated to all nodes in a dynamic network (as introduced by Kuhn et al., STOC 2010). In contrast to general dynamic networks, our dynamic networks are unit disk graphs, i.e., nodes are embedded into the Euclidean plane and two nodes are connected if and only if their distance is at most R. Our worst-case adversary is allowed to move the nodes on the plane, but the maximum velocity v_max of each node is limited and the graph must be connected in each round. For this model, we provide almost tight lower and upper bounds for k-token dissemination if nodes are restricted to send only one token per round. It turns out that the maximum velocity v_max is a meaningful parameter to characterize dynamics in our model.

Three-Valued Abstraction and Heuristic-Guided Refinement for Verifying Concurrent Systems - Timm, Nils
Software systems are playing an increasing role in our everyday life, and as the amount of software applications grows, so does their complexity and the relevance of their computations. Software components can be found in many systems that are charged with safety-critical tasks, such as control systems for aviation or power plants. Hence, software verification techniques that are capable of proving the absence of critical errors are becoming more and more important in the field software engineering. A well-established approach to software verification is model checking. Applying this technique involves an exhaustive exploration of a state space model corresponding to the system under consideration. The major challenge in model checking is the so-called state explosion problem: The state space of a software system grows exponentially with its size. Thus, the straightforward modelling of real-life systems practically impossible. A common approach to this problem is the application of abstraction techniques, which reduce the original state space by mapping it on a significantly smaller abstract one. Abstraction inherently involves a loss of information, and thus, the resulting abstract model may be too imprecise for a definite result in verification. Therefore, abstraction is typically combined with abstraction refinement: An initially very coarse abstract model is iteratively refined, i.e. enriched with new details about the original system, until a level of abstraction is reached that is precise enough for a definite outcome. Abstraction refinement-based model checking is fully automatable and it is considered as one of the most promising approaches to the state explosion problem in verification. However, it is still faced with a number of challenges. There exist several types of abstraction techniques and not every type is equally well-suited for all kinds of systems and verification tasks. Moreover, the selection of adequate refinement steps is nontrivial and typically the most crucial part of the overall approach: Unfavourable refinement decisions can compromise the state space-reducing effect of abstraction, and as a consequence, can easily lead to the failure of verification. It is, however, hard to predict which refinement steps will eventually be expedient for verification – and which not.

Symbiotic Coupling of P2P and Cloud Systems: The Wikipedia Case - Graffi, Kalman; Bremer, Lars (Proceedings of the International Conference on Communications (ICC'13))
Cloud computing offers high availability, dynamic scalability, and elasticity requiring only very little administration. However, this service comes with financial costs. Peer-to-peer systems, in contrast, operate at very low costs but cannot match the quality of service of the cloud. This paper focuses on the case study of Wikipedia and presents an approach to reduce the operational costs of hosting similar websites in the cloud by using a practical peer-to-peer approach. The visitors of the site are joining a Chord overlay, which acts as first cache for article lookups. Simulation results show, that up to 72% of the article lookups in Wikipedia could be answered by other visitors instead of using the cloud.

Service Matching under Consideration of Explicitly Specified Service Variants - Platenius, Marie Christin; von Detten, Markus; Gerth, Christian; Schäfer, Wilhelm; Engels, Gregor (IEEE 20th International Conference on Web Services (ICWS 2013))
One of the main ideas of Service-Oriented Computing (SOC) is the delivery of flexibly composable services provided on world-wide markets. For a successful service discovery,service requests have to be matched with the available service offers. However, in a situation in which no service that completely matches the request can be discovered, the customer may tolerate slight discrepancies between request and offer. Some existing fuzzy matching approaches are able to detectsuch service variants, but they do not allow to explicitly specify which parts of a request are not mandatory. In this paper, we improve an existing service matching approach based onVisual Contracts leveraging our preliminary work of design pattern detection. Thereby, we support explicit specifications of service variants and realize gradual matching results that can be ranked in order to discover the service offer that matches a customer’s request best.

Semi-Automated Software Composition Through Generated Components - Mohr, Felix; Kleine Büning, Hans (Proceedings of the 15th International Conference on Information Integration and Web-based Applications & Services (iiWAS))
Software composition has been studied as a subject of state based planning for decades. Existing composition approaches that are efficient enough to be used in practice are limited to sequential arrangements of software components. This restriction dramatically reduces the number of composition problems that can be solved. However, there are many composition problems that could be solved by existing approaches if they had a possibility to combine components in very simple non-sequential ways. To this end, we present an approach that arranges not only basic components but also composite components. Composite components enhance the structure of the composition by conditional control flows. Through algorithms that are written by experts, composite components are automatically generated before the composition process starts. Therefore, our approach is not a substitute for existing composition algorithms but complements them with a preprocessing step. We verified the validity of our approach through implementation of the presented algorithms.

Seitenkanalresistenz paarungsbasierter Kryptographie - Otte, Oliver

Security Proofs for Pairing-Based Cryptography in the Generic Group Model - Bobolz, Jan

Securing Critical Unattended Systems with Identity Based Cryptography - A Case Study - Blömer, Johannes; Günther, Peter; Krummel, Volker (Proceedings of the 5th International Conference on Mathematical Aspects of Computer and Information Sciences (MACIS))
Unattended systems are key ingredients of various critical infrastruc-tures like networks of self service terminals or automated teller machines.For cost and efficiency reasons they should mostly run autonomously.Unattended systems are attractive and lucrative targets for various kindsof attacks, including attacks on the integrity of their components and thecommunication between components. In this paper, we propose a gen-eral cryptographic framework to protect unattended systems. We alsodemonstrate that instantiating the framework with techniques from iden-tity based cryptography is particularly well-suited to efficiently secureunattended systems.

Routing in heterogenen OpenFlow Netzwerken - Wallaschek, Felix

Ressource-Optimized Deployment of Multi-Tier Applications - The Data Rate-Constrained Case - Robbert, Christoph

Reengineering of Component-Based Software Systems in the Presence of Design Deficiencies - von Detten, Markus
The maintenance of component-based software systems requires up-to-date models of their concrete architecture, i.e. the architecture that is realised in the source code. These models help in systematically planning, analysing and executing typical reengineering activities. Often no or only outdated architectural models of such systems exist. Therefore, various reverse engineering methods have been developed which try to recover a system's components, subsystems and connectors. However, these reverse engineering methods are severely impacted by design deciencies in the system's code base, especially violations of the component encapsulation. As long as design deciencies are not considered in the reverse engineering process, they reduce the quality of the recovered component structures. Despite this impact of design deciencies, no existing architecture reconstruction approach explicitly integrates a systematic deciency detection and removal into the recovery process. Therefore, I have developed Archimetrix. Archimetrix is a tool-supported architecture reconstruction process. It enhances a clustering-based architecture recovery approach with an extensible, pattern-based deciency detection. After the detection of deciencies, Archimetrix supports the software architect in removing the de ciencies and provides the means to preview the architectural consequences of such a removal. I also provide a process to identify and formalise additional deciencies. I validated the approach on three case studies which show that Archimetrix is able to identify relevant deciencies and that the removal of these deciencies leads to an increased quality of the recovered architectures, i.e. they are closer to the corresponding conceptual architectures.

Reducing Nondeterminism in Automated Service Composition - Mohr, Felix; Lettmann, Theodor; Kleine Büning, Hans (Proceedings of the 6th International Conference on Service Oriented Computing and Applications (SOCA))
Automated service composition has been studied as a subject of state based planning for a decade. A great deal of service composition tasks can only be solved if concrete output values of the services are considered in the composition process. However, the fact that those values are not known before runtime leads to nondeterministic planning problems, which have proven to be notoriously difficult in practical automated service composition applications. Even though this problem is frequently recognized, it has still received remarkably few attention and remains unsolved.This paper shows how nondeterminism in automated service composition can be reduced. We introduce context rules as a means to derive semantic knowledge from output values of services. These rules enable us to replace nondeterministic composition operations by less nondeterministic or even completely deterministic ones. We show the validity of our solutions not only theoretically but also have evaluated them practically through implementation.

Reactive Planar Spanner Construction in Wireless Ad Hoc and Sensor Networks - Benter, Markus; Neumann, Florentin; Frey, Hannes (Proceedings of the 32nd IEEE International Conference on Computer Communications (INFOCOM))
Within reactive topology control, a node determines its adjacent edges of a network subgraph without prior knowledge of its neighborhood. The goal is to construct a local view on a topology which provides certain desired properties such as planarity. During algorithm execution, a node, in general, is not allowed to determine all its neighbors of the network graph. There are well-known reactive algorithms for computing planar subgraphs. However, the subgraphs obtained do not have constant Euclidean spanning ratio. This means that routing along these subgraphs may result in potentially long detours. So far, it has been unknown if planar spanners can be constructed reactively. In this work, we show that at least under the unit disk network model, this is indeed possible, by proposing an algorithm for reactive construction of the partial Delaunay triangulation, which recently turned out to be a spanner. Furthermore, we show that our algorithm is message-optimal as a node will only exchange messages with nodes that are also neighbors in the spanner. The algorithm’s presentation is complemented by a rigorous proof of correctness.

Programs from Proofs – A PCC Alternative - Wonisch, Daniel; Schremmer, Alexander; Wehrheim, Heike (Proceedings of the 25th International Conference on Computer Aided Verification (CAV))
Proof-carrying code approaches aim at safe execution of untrusted code by having the code producer attach a safety proof to the code which the code consumer only has to validate. Depending on the type of safety property, proofs can however become quite large and their validation - though faster than their construction - still time consuming. In this paper we introduce a new concept for safe execution of untrusted code. It keeps the idea of putting the time consuming part of proving on the side of the code producer, however, attaches no proofs to code anymore but instead uses the proof to transform the program into an equivalent but more eﬃciently veriﬁable program. Code consumers thus still do proving themselves, however, on a computationally inexpensive level only. Experimental results show that the proof eﬀort can be reduced by several orders of magnitude, both with respect to time and space.

Profitable Scheduling on Multiple Speed-Scalable Processors - Kling, Peter; Pietrzyk, Peter (Proceedings of the 25th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
We present a new online algorithm for profit-oriented scheduling on multiple speed-scalable processors.Moreover, we provide a tight analysis of the algorithm's competitiveness.Our results generalize and improve upon work by \citet{Chan:2010}, which considers a single speed-scalable processor.Using significantly different techniques, we can not only extend their model to multiprocessors but also prove an enhanced and tight competitive ratio for our algorithm.In our scheduling problem, jobs arrive over time and are preemptable.They have different workloads, values, and deadlines.The scheduler may decide not to finish a job but instead to suffer a loss equaling the job's value.However, to process a job's workload until its deadline the scheduler must invest a certain amount of energy.The cost of a schedule is the sum of lost values and invested energy.In order to finish a job the scheduler has to determine which processors to use and set their speeds accordingly.A processor's energy consumption is power $\Power{s}$ integrated over time, where $\Power{s}=s^{α}$ is the power consumption when running at speed $s$.Since we consider the online variant of the problem, the scheduler has no knowledge about future jobs.This problem was introduced by~\citet{Chan:2010} for the case of a single processor.They presented an online algorithm which is $α^{α}+2eα$-competitive.We provide an online algorithm for the case of multiple processors with an improved competitive ratio of $α^{α}$.

Software Engineering for Self-Adaptive Systems: A Second Research Roadmap - de Lemos, Rogrio; Giese, Holger; A. Müller, Hausi; Shaw, Mary; Andersson, Jesper; Litoiu, Marin; Schmerl, Bradley; Tamura, Gabriel; M. Villegas, Norha; Vogel, Thomas; Weyns, Danny; Baresi, Luciano; et al. (Software Engineering for Self-Adaptive Systems II)

Leichtgewichtige Traceability im agilen Entwicklungsprozess am Beispiel von Scrum - Bouillon, Elke; Güldali, Baris; Herrmann, Andrea; Keuler, Thorsten; Moldt, Daniel; Riebisch, Matthias (Softwaretechnik-Trends)